Changes in Retinal Vasculature and Thickness after Small Incision Lenticule Extraction with Optical Coherence Tomography Angiography. (20th May 2019) - Chen, Minjie; Dai, Jinhui; Gong, Lan
Abstract : Purpose . To evaluate the changes in retinal vessel density and thickness after small incision lenticule extraction (SMILE) with optical coherence tomography angiography (OCTA) in myopic patients. Methods . In this prospective study, SMILE surgeries were done in 46 eyes of 24 patients with spherical equivalent (SE) more than −6.0 diopters ( D ). Retinal vessel density and thickness at the macula and optic nerve were recorded with OCTA before and 1 day, 2 weeks, and 1 month after surgery. Intraocular pressure (IOP), uncorrected distance visual acuity (UDVA), and refraction were taken at the same time. Results . The superficial retinal vessel density and deep foveal retinal vessel density 1 day after surgery were less than those before surgery; however, the changes at any timepoints were not statistically significant (p = 0.2736 andp = 0.1590, respectively). Both the superficial vessel density and deep vessel density at the parafoveal and perifoveal regions decreased significantly 1 day postoperatively (allp < 0.05 ) and then returned to the preoperative level at 2 weeks and stabilized thereafter. There were no significant changes in any of the 4 vessel densities in the area of peripapillary before and 1 day, 2 weeks, and 1 month after surgery (p = 0.3345 ). No statistically significant differences between preoperative and postoperative retinal thickness were detected for the area of macula and optic nerve (allp > 0.5 ). Conclusions . The vessel density at the parafoveal and perifoveal regions decreased at 1 day after SMILE with no effect on the visual acuity and relieved within 2 weeks. Decreased ocular blood flow in response to the spike in IOP may account for such changes.